Alumina coating of polyvinylidene fluoride (PVDF) surface in liquid phase. (April 2014) - Liiv, J.; Panov, D.; Tenno, T.; Järv, J.
<x content-type="archive" xml:space="preserve">Abstract</x> A two-step procedure is developed for preparing alumina coated polyvinylidene fluoride particles (diameter, ∼100 μm) whose chemically inert and non-adhesive surface is initially grafted with polystyrene. The first coating step involves deposition of alumina precipitation centres into the polystyrene layer using the reaction of trimethylaluminium with a small residual amount of water retained within the porous brushy polystyrene structure after incomplete drying of the particles. The second coating step is performed through gentle precipitation of aluminium hydroxide from an aqueous aluminium chloride solution, with the alumina deposition being directed by the precipitation centres implanted during the first step. As a result of this process, the particles are covered uniformly with inorganic material. The quality and thickness of the final coating layer are controlled by the precipitation rate and stirring conditions.